Biopolymers As Smart Drug Carriers in Cancer Therapy: Innovations and Perspectives - Malek Mohammadi, Nazanin (Biocompounds, 2025)
Cancer continues to pose a major global health burden, largely due to the limitations of conventional therapies, including non-specific drug distribution, systemic toxicity, and the emergence of multidrug resistance. Biopolymer-based smart drug delivery systems have emerged as promising platforms that can enhance tumor selectivity and therapeutic efficacy while reducing adverse effects. Natural and synthetic biopolymers offer key advantages, including biocompatibility, controlled biodegradability, tunable surface functionality, and the ability to form diverse nanoscale architectures that enable precise drug loading and targeted release. Recent advances have demonstrated the potential of biopolymer-derived nanoparticles, micelles, hydrogels, nanogels, and polymer-drug conjugates to respond to tumor-specific stimuli, including pH gradients, enzymatic activity, hypoxia, and external triggers. This review highlights major classes of biopolymers, design strategies for targeted and stimuli-responsive delivery, and their therapeutic applications across chemotherapy, gene delivery, and immunomodulation. Key challenges such as scalability, stability, and clinical translation are critically examined, and future perspectives are provided to guide the development of next-generation biopolymer-based smart carriers for precision cancer therapy.